Pelayanan terbitan berseri dan manfaat jurnal bagi pemustaka - Mohammad Mansyur; Aries Hamidah; Muchamad Muhsinun (IJAL (Indonesian Journal of Academic Librarianship), 2022)
One of the library collections, which must also be owned and become the concern of the manager is a type of collection of serial publications or periodicals. That is a type of collection that has special characteristics, such as a high level of proficiency compared to a monograph collection, published continuously. Among the types of collections that must receive serious attention from the library manager are types of serial publications that have a high level of proficiency and provide space for the delivery of ideas / ideas quickly, support and facilitate research, also add insight.